DETERMINAN TINGKAT KEMISKINAN KABUPATEN/KOTA DI PROVINSI NUSA TENGGARA TIMUR - Agnes Nadia Prasetyana Siba Sabon; I Nyoman Mahaendra Yasa (CV. ADIBA AISHA AMIRA, 2025)
Poverty is a multidimensional problem that not only affects economic aspects but also has serious implications for the social, political, and quality of development in a region. In East Nusa Tenggara Province, poverty remains a major challenge for complex and sustainable regional development. The high poverty rate in this region is often associated with suboptimal labour market conditions, low levels of education, and minimum wages that do not fully reflect the cost of living. Therefore, an in-depth study is needed to determine the extent to which these factors influence poverty levels at the district/city level. This study aims to analyse the influence of the variables of labour force size, education level, and district minimum wage (UMK) on poverty levels in 22 districts/cities in East Nusa Tenggara Province from 2019 to 2024. The method used in this study is a quantitative approach with an associative research design. The data analysed are panel data, consisting of a combination of cross-sectional data from 22 districts/cities and time-series data from 2019 to 2024, resulting in a total of 132 observations. To obtain accurate analysis results, a panel data regression model with a random effect model (REM) approach was used, selected based on the results of the Hausman test. The analysis results indicate that simultaneously, the three independent variables, namely labour force, education level, and district minimum wage, have a significant impact on the poverty rate of districts/cities in East Nusa Tenggara Province. Partially, the variables of labour force and education level have a negative and significant impact, meaning that an increase in the number of absorbed labour force and an increase in the education level of the community will reduce the poverty rate. Similarly, the minimum wage in the district also has a negative and significant effect on poverty, indicating that an increase in the minimum wage contributes to a decrease in the number of poor people, especially in districts/cities in East Nusa Tenggara Province.